Impact of Edge Computing Paradigm on Energy Consumption in IoT. Issue 6 (2018) - Mocnej, Jozef; Miškuf, Martin; Papcun, Peter; Zolotová, Iveta
Abstract: The exponential growth of devices connected to the Internet, the diversity of the Internet of Things (IoT) paradigm, and the variety of IoT protocol stacks are all factors arising concerns about IoT sustainability. A promising solution seems to be IoT integration platforms, which provide the foundation for managing connected devices in a standardized way. The first wave of IoT platforms has been driven by cloud computing with all the logic in the cloud, yet taking a part of the logic to the edge might be a more suitable approach for many use cases. The edge computing paradigm is going to be the next step in the evolution of IoT platforms, but its initial complexity requires further research work to fully comprehend all potential benefits. This paper describes the utilization of edge computing in the IoT and analyzes its impact on energy consumption of IoT devices. The practical case study provided in this paper evaluates the overhead caused by computation at the edge and presents a possible implementation of the edge computing paradigm to positively influence the lifespan of constrained devices powered by batteries.